Exploring ecotoxicological fish bioassay for the evaluation of uranium reprotoxicity. (11th June 2014) - Simon, Olivier; Floc'h, Estelle; Geffroy, Benjamin; Frelon, Sandrine
Abstract Although reproduction in fish is known to be sensitive to metal exposure, few ecotoxicological studies have focused on the toxicological effects of metals. Because uranium (U) is naturally present in aquatic ecosystems (0.6–2 mg/L), freshwater organisms are subjected to chronic U exposure. Although new standardized assays are currently being developed to mimic realistic exposure conditions, they could be improved by taking into account the contamination that occurs throughout the life cycle of fish. The authors initially evaluated the effect of food (commercial flakes vs pure Spirulina) and ionic composition of the exposure medium on the reproductive performance of Danio rerio. The effects of U exposure on reproduction then were assessed 1) for the F0 adult stage at short exposure times (5 d, 20 d, and 40 d), and 2) for the F0 stage and the F1 generation after 200 d of exposure to control, low (20 µg U/L), and moderate (250 µg U/L) waterborne levels of U. Reproductive endpoints (reproductive success, fecundity, number of spawns, egg and larvae viability, and hatching) were measured mainly after the first spawn and after 10 d of cumulative spawns. The authors evaluated the plasticity of these endpoints and compared the effect of exposure conditions to identify the most relevant markers of the effect of U exposure on reproductive performance of D. rerio. Environ Toxicol Chem 2014;33:1817–1824. © 2014 SETAC